THE CYTOTOXIC ACTIVITY OF ETHYLACETATEFRACTION OF KERSEN (Muntingia Calabura) LEAVES AGAINST LARVAE SHRIMP ARTEMIA SALINA LEACH - Sadli .; Nurul Wahyu Utami; Irma Sari (Jurnal Natural, 2015)
Abstract. The cytotoxic activity experiment of ethylacetatefraction of kersen (Muntingia calabura) leaves has been carried out using the Brine Shrimp Lethality Test (BSLT) method withf ive concentration variables; they are 10 ppm, 100 ppm, 200 ppm, 500 ppm, and 1000 ppm. The research aims to determine the secondary metabolite; the extract characterization and determine cytotoxic activity of the ethyl acetate fraction of kersen (Muntingia calabura L.) leaves. Extraction was done with maceration method using ethyl acetate solvent to the kersen dried leaves dregs of n-hexane extract and the value of LC50 was determine by using probit analysis. The results of phytochemical screening showed that ethyl acetate fraction of kersen (Muntingia calabura) leaves contained three secondary metabolites, namely tannin, saponin and flavonoid with extract characterization results are the water content of 3.85%3 ± 0.35%, the water soluble extractive of 17.65% ± 0.27%, ethanol soluble extractive of 62.24% ± 0.07%, the total ash value of 0.89%± 0.005%, and acid insoluble ash value of 0.69%± 0.004%. The LC50 value of ethyl acetate fraction of kersen (Muntingia calabura) 84.92 ppm showed that the extract has  cytotoxic activity as medium toxic.